HUBUNGAN PELAKSANAAN KOMUNIKASI TERAPEUTIK PERAWAT DENGAN TINGKAT KEPUASAN PASIEN DI RUANG PERAWATAN PENYAKIT DALAM RUMAH SAKIT MISI LEBAK - Rochani, Siti (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2019)
Nurse therapeutic communication in order to give comfort and satisfaction to the patients is very urgent in healing process. There are many patients complaining about satisfaction of nurse therapeutic communication. This research aimed to know the relation of nurse?s therapeutic communication to the satisfaction of the patients that running a medical treatment in the caring room  of Misi Lebak Hospital. The research followed a quantitative analytic method with a cross sectional design.  The research was applied in internal illness caring room in Misi Lebak Hospital during May to June 2017 with amount of 52 sampling  as internal illness patients that  following a medical treatment in the internal illness caring room of Misi Lebak Hospital. The result showed that most of the respondent as much 36 respondents (69,2%) said that the nurse?s therapeutic communication in good category and 16 other respondents (30,8%) said that nurse?s therapeutic communication in less category. And by the patient satisfaction degree to the nurse therapeutic communication in any phase of therapeutic, whether orientation phase, working phase or termination phase most of the respondent felt satisfied (69,2%) and 3,8% felt unsatisfied. And statistically, the result showed that there was a significant relation between therapeutic communication to the patient satisfaction in internal illness caring room in Misi Lebak Hospital (p value 0.010). Then the research suggested that Misi Lebak Hospital should improve nurse?s skill to increase a better therapeutic communication.   Key words : therapeutic, nurse, communication, satisafaction, patient